Bean production systems Germplasm discipline : A status report - Burns, R. (International Center for Tropical Agriculture, 1976)
A report is given on the organization of CIAT`s bean germplasm bank, which main objectives are: (1) assemble the world`s available genetic resources of beans for the basic and applied research to raise bean production in the tropics; (2) characterize systematically each entry and record its morpho-agronomic traits to make such information available to interested researchers; and (3) produce and preserve enough seed of each entry to supply bean researchers. The no. of seed samples obtained in 1970-76 from different countries is indicated, the operating system of the germplasm bank is described, and the morpho-agronomic parameters used to characterize each entry are defined. These are recorded for the computer using the Statistical Analysis System (SAS). Seed handling is described and future plans and needs are discussed. (CIAT)